A consideration of the lasting effects of a course introducing ethical issues in computing - Joyce, Daniel T. (2012)
We discuss the objectives of a course for computer science majors that introduces ethical issues in computing. In particular we are interested – as an exceptional matter – in the long term objectives. We pose and attempt to answer [or at least discuss] the following questions: What effects are we hoping such a course has on its participants five, ten, twenty years down the road? How can our contemplation of these issues inform our pedagogy? How can we design this course so that is has a lasting impact on the students?